Perbandingan Pengaturan Hak Cipta Karya Potret Ditinjau dari Hukum Indonesia dan Jepang - Anissa Maya Hapsari; Diana Tantri Cahyaningsih (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The increasing ease of interaction, which is becoming more intensive, extensive, and unrestricted, is a result of technological advancements. This is accompanied by the advancement of human thinking, which can create new innovations. These innovations are subsequently embodied in works, one of which is portrait works. The works that result from such innovations are protected as Copyrights in the form of Portrait Rights. The background for selecting Japan as the country for comparison is based on data from the Intellectual Property Index, where Japan scores higher in terms of copyright protection compared to Indonesia, with scores of 8.1 and 3.9, respectively. This study aims to understand the comparison of copyright regulations related to portrait rights and the efforts that can be made through this comparison to achieve legal certainty. This research is normative legal research that uses a statute approach and a comparative approach. The results of this study show similarities regarding the international agreement ratified by both countries and differences in the types of rights in their copyright regulations. Furthermore, effort to achieve legal certainty related to the theory of progressive law include continually updating regulations to align with societal development, as the law has a dynamic nature